A Single-Center Experience With Percutaneous Interventional Management of Refractory Chylous Ascites. Issue 4 (November 2021) - Tai, Elizabeth; Min, Adam; Rajan, Dheeraj K.
Purpose: Management of chylous ascites is poorly understood with no management guidelines. We retrospectively reviewed patients treated for chylous ascites at our institution to evaluate efficacy and safety of lipiodol lymphangiography and embolization. Materials and Methods: Seven patients underwent percutaneous interventional management of chylous ascites (average age 52.5 years, 3 female, 6 post-surgical, 1 pancreatitis) from 2012. All patients underwent lipiodol inguinal lymph node injection. Adjunctive glue embolization was performed if a leak was identified. Data were collected on the cause of chylous ascites, conservative management strategies, procedural details, and success. Results: All patients had chylous ascites refractory to conservative management. Preprocedure lymphoscintigraphy identified a retroperitoneal leak in 6 patients. Seven patients underwent 12 lymphangiogram procedures; 8 were performed at our institution. Lymphangiography identified a leak in 5 patients (71%). Success was achieved in 2 patients (28%) treated at our institution after glue embolization following cannulation of the leaking lymphatic channels and 1 patient (14%) after lymphangiography alone for an overall success rate of 43% (3/7). Two patients (29%) were successfully treated after one procedure. Two patients (29%) unsuccessfully treated at our institution were referred to a specialized center in the United States. No 30 day post procedural complications. Conclusions: In our experience, lymphangiography and embolization was a safe, relatively effective and minimally invasive method for treating medically refractory chylous ascites. Complex cases required referral to a specialized institution with resources unavailable at our tertiary care center.